2021
DOI: 10.23923/j.rips.2022.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la prevalencia de las tácticas empleadas por los adolescentes ecuatorianos para la resolución de conflictos en el noviazgo

Abstract: RESUMEN. Objetivo: Se diseñó un estudio de campo con el objetivo de conocer la prevalencia de las tácticas usadas para la resolución de los conflictos en el noviazgo, la asociación con el género, la direccionalidad y la frecuencia de uso en una muestra de adolescentes de Quito (Ecuador). Método: Participaron en el estudio un total de 985 adolescentes con edades de 13 a 19 años (M = 15.02, DT = 1.72) que respondieron a la adaptación española de la Modified Conflict Tactics Scale referido a las relaciones de nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The findings coded as "patriarchal culture" are consistent with those of various studies that have found an association between violence in dating relationship, sexism, and romantic love [7,19]; an association between romantic love, blaming the victim and legitimization of the violence [20]; an intergenerational transmission of violence, where it is learned that violence is appropriate for conflict resolution [21][22][23]; and the belief that "good jealousy" exists, understood as a game that serves to measure how much love or interest one person, when provoked, has for the other, who has initiated the game, which is common among adults [24]. We learned in the focus groups that this pattern is being reproduced by adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…The findings coded as "patriarchal culture" are consistent with those of various studies that have found an association between violence in dating relationship, sexism, and romantic love [7,19]; an association between romantic love, blaming the victim and legitimization of the violence [20]; an intergenerational transmission of violence, where it is learned that violence is appropriate for conflict resolution [21][22][23]; and the belief that "good jealousy" exists, understood as a game that serves to measure how much love or interest one person, when provoked, has for the other, who has initiated the game, which is common among adults [24]. We learned in the focus groups that this pattern is being reproduced by adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…Other less worrying issues were the family and social relations of parents (e.g., relation with the other parent, new partner, behaviour of the other parent, adjustment of the other parent, extended family), work (e.g., balancing work and family life, having a stable job and income), legal issues (e.g., related to child custody, alimony, visiting rights and reported offences to the police), and psychological and emotional factors (e.g., negative emotions, feelings of guilt, loss of love/affection, feeling lonely). Thus, the breakup issues that most concerned parents were their children's health, behaviour, family relations, and academic performance and failure that correspond precisely to the areas of child development that the literature has identified with harm associated to parental breakup (Alonso & Romero, 2021;Corrás et al, 2017;Martinón et al, 2017;Seijo et al, 2016;Torres et al, 2022).…”
Section: Needs and Desiderata Of Users Of The Psnfb Programmentioning
confidence: 99%